Implementasi Kebijakan Transfer Anggaran Provinsi Berbasis Ekologi (TAPE) Di Kalimantan Utara - Erika Nur Khasanah; Dini Gandini Purbaningrum; Abdul Rahman; Evi Satispi (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The purpose of this research is to find out how to implement the Ecological-Based Provincial Budget Transfer Policy (TAPE) in North Kalimantan Province. This research uses qualitative research methods with a descriptive approach. The data obtained is carried out through observations, interviews, and documentation. The theory used in analysis is the Merilee S theory. Grindle determined by the content of policy (content of policy) and context of its implementation (context of implementation). The results of the study show that the interests that affect this policy are the interests of the provincial government because this policy is made purely looking at the natural conditions in North Kalimantan Province that prioritise the interests of the community. Then the type of benefits of this policy shows that with this policy, there are many benefits for both the Regency/City government and the community. The degree of change that occurred after this policy was also felt by both the Regency/City government and the community. The location of the decision making is still considered not optimal because the decision of this TAPE policy is only carried out by the Provincial government. In addition, the implementation of the program is still considered not optimal because there are still obstacles faced and the unfulfillment of all the criteria and indicators that have been given. Then, the resources are still inadequate, both human resources, and budget resources. For power, it is quite good seen from the communication and coordination of each agency. As for the characteristics, it is also considered good in policy implementation. Compliance and response are carried out by the Regency/City and the community which in this case is good enough.